(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The technology of using humic acid substance in agricultural application is a completely unexplored area that is expected to expand in the future, in addition to expecting excellent application for this technology in the field of fertilizer manufacturing, reduce the quantities of chemical fertilizers add to the soil, decreasing the rates of pollution with their residues, and preserving the environment. So this review study came to highlight the impact of humic acid application as one of the importance humic substances on different field crops production, through its essential role in improving plant nutrition and soil fertility, and it’s characterized by its low price, ease of use, and lack of environmental pollution and crops products. Humic acid contributes to improving many soil biological, physical, chemical and organically properties compared to chemical fertilizers, which have positive influence on crop growth and production, therefore application of humic acid in crop fertilization it is possible to decrease chemical fertilizers application even partially, with reduce cultivation cost and enhance role in mitigation of harmful impacts of abiotic stress causes by drought, high temperatures and salinity. In this literature review has been summarized the impact of humic acid application on various field crops traits such seedling and crop growth, crop productivity, seeds quality, and nutrients uptake and availability in the soil, when humic acid applied in any method by seeds soaking, soil application and foliar application.